THE EFFECT OF ZAKAT AND CORPORATE SOCIAL RESPONSIBILITY (CSR) ON THE LEVEL OF SOCIAL INEQUALITY IN INDONESIA - ATKIYAN, FAHRUL; Hudatil Atkiyan, Fahrul (GEMOVE: Journal of Gender, Movement, and Empowerment, 2025)
Social inequality is one of the problems that a country must face. One of the ways used to overcome poverty is by using zakat and corporate social responsibility (CSR) instruments. In this study, the author will discuss the influence of zakat and CSR in alleviating poverty. This study uses a quantitative method, and from the results of testing with the quantitative method, it can be concluded that zakat has a positive but not significant effect, and corporate social responsibility (CSR) has no significant effect in alleviating poverty in Indonesia.